MALAYSIA-INDONESIA BILATERAL RELATIONS: EMPIRICAL STUDY ON THE STAGE OF KNOWLEDGE OF GENERATION X AND Y INDONESIA AND MALAYSIA - Rohani Hj. Ab Ghani; Ahmad Shukri bin Abdul Hamid; Zulhilmi bin Paidi; Mohd Kasri bin Saidon; Haslinda Hasan; Kamaruddin Ahmad; Muhaemin Latif (Universitas Islam Negeri Alauddin Makassar, 2021)
Malaysia and Indonesia are traditionally neighboring countries in ASEAN and sharing a historical background, language, culture, and religion. It is undeniable fact that Malaysia-Indonesia relations are often influenced by current national issues such as water territorial, Indonesian immigrants, national product, and others. Reviews These issues always sparked conflicts and Provoked various actions from Indonesians and dieting. Normally, Indonesians are more sensitives compared with dieting when faced with this situation as well. This article focuses on knowledge and understanding of X and Y Indonesian generation on Malaysia-Indonesia bilateral relations. This article incorporates the qualitative method with primary data obtained through a questionnaire distributed amongst respondents. Respondents are consisted of UIN's first-degree students and staff s and were selected by purposive sampling. Apart from that, focus group discussion and interview session was held to get a view from respondents. This article found that X and Y Indonesian generations have a good understanding of Malaysia. They are also usually aware of the importance of Malaysia-Indonesia bilateral relations. In addition, they acknowledged Malaysia as an essential country for Indonesia's present interest. Respondents also showed high sensitivity regarding competition between Malaysia and Indonesia. The important finding of this writing is both generations s acknowledge the fact that they are closest neighboring country and a good relationship should be maintained in facing the global challenge